Impact of deforestation in Ethiopia - Kasu Hailu Biru (Journal of the Selva Andina Biosphere)
Ethiopia is an agrarian country with a notable topographic variety from 110m below sea level at Dalol Depression to 4620m above sea stage at Mount Ras Dashin. Because of its topographic variation and area within the tropics, Ethiopia has diverse weather situations and the ensuing numerous ecosystems. As an end result, the country Is nicely endowed in natural resources. However, deforestation has long gone for the closing five decades. Forests which were above 40 % of the country’s landmass in the beginning of 20th century are reduced into 2.36 % in 2000. Deforestation has many negative consequences including the loss of biodiversity, climate change, and degradation of soils, disruption of hydrological cycles, desertification, economic loss, and social conflicts. The rate of deforestation is often bogged down considerably and its negative socioeconomic and environmental impacts are often minimized through improved protection and management of the remaining forests, well-targeted socioeconomic improvement initiative, and via policy and organization reforms. Developing countries, like Ethiopia, are highly susceptible to the impacts of global climate change due to their limited potential to mitigate and adapt. Therefore, the subsequent mitigation measures are mandatory to save lots of the country. These are providing energy sources, conserving the remaining natural forests, market plantations, and regeneration of abandoned agricultural fields.